Ra223 in bone metastases with osteolytic activity - Costa, Renato; Cardile, Davide; Murabito, Alessandra; Tripoli, Vincenzo; Verderame, Francesco (World Journal of Nuclear Medicine, 2018)
Radium 223 dichloride (Ra223) is the only targeted alpha therapy able to extend survival in patients with bone metastases from prostate cancer. Mechanism of action and data currently available focused mainly on osteoblastic metastases from prostate cancer. In our institution, a patient with breast cancer affected by osteolytic metastases was treated with off-label use of Ra223. The evaluation of the deposit areas of Ra223 showed a perfect overlap with the regions of osteolysis previously detected by scintigraphy, indicating a possible therapeutic effect. This case report is the first document attesting Ra223 deposit in osteolytic metastases opening new opportunity of therapeutic development for this radiopharmaceutical.
Keywords: Bone metastases; breast cancer; osteoblastic bone metastases; osteolytic bone metastases; radium 223